(untitled) (Global Journal of Human-Social Science, 2026)
The essay explores the creative praxis of everyday life as a fundamental element for individual and collective human existence. Starting from philosophical and sociological perspectives (Lalive D’Epinay, Maturana, Innerarity), the authors analyze how everyday life, understood as a space between routines and events, can be a source of both creativity and plenitude as well as oppression and alienation. Techno-economic globalization is criticized and the paradox of a hyperconnected world that generates solitude and automatism is highlighted. The study reveals scarce studies on everyday creativity (e.g. only 1 thesis in Teseo), but also recent work (Scopus, Science) linking creative activities with psychological well-being, resilience and social transformation. Faced with challenges such as the digital era, algorithms and AI, an education based on autonomy, critical thinking and complexity (Morin) is proposed, which promotes "vital motricity", based on a balance between survival and fulfillment. The essay concludes with a call to celebrate daily creativity, resist dehumanization and inhabit "matters" between productivity and meaning, without falling into polarization.